Editing JAT and enabling publication: an afterword. Issue 1 (20th March 2017) - Abbott, Chris
Abstract : Purpose: An afterword from the previous editor of this journal, looking back at what has been notable and ahead to what seem to be likely changes in the future. The paper aims to discuss this issue. Design/methodology/approach: Overview of key issues in the first ten years of the Journal of Assistive Technologies. Findings: Some key issues are identified and likely future foci are tentatively suggested. Originality/value: An editorial perspective.